(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In the littoral area of Buenos Aires province two carbonate Quaternary lithostratigraphic units linked to marine transgressions are found. In the most recent unit (Las Escobas Formation, Holocene) lithogenic calcareous soils (Calciudolls and Rendolls) are developed, which have been studied in their taxonomic, mineralogical and micromorphologic aspects (Vargas Gil et al., 1972; Sánchez, 1976; Imbellone, 1996; Imbellone and Giménez, 1997; 1998). Conversely, little information on the soils associated to the oldest unit (Pascua Formation, middle to upper Pleistocene) is available. This unit is interbedded in the upper part of the loessial sediments of the Pampiano Formation, consisting of sandy sediments with high amounts of mollusk shells strongly cemented with calcium carbonate forming a coquina (Fidalgo et al., 1973). These deposits are overlain by sediments of the Pampiano Formation, over 2 m in thickness, where Mollisols and Vertisols have been affected by calcification, vertisolization and clay illuviation processes. The objectives of this article are: a) to analyze the properties of the soils developed in loessic sediments overlying the Pascua Formation, and b) to estimate the influence of the carbonate deposits of this formation in the soil genesis. Five pedons (four Mollisols and one Vertisol) located in the municipalities of La Plata, Magdalena and Punta Indio (Buenos Aires province, Argentina, Fig. 1) were studied. The soils have developed in an upland plain adjacent to coastal plains. The climate is temperate-humid, with a mean annual rainfall of 1040 mm, fairly well distributed; mean annual temperature is 16.2 oC (La Plata city, latitude 34o 55’ S, longitude 57o 56’ W, altitude 15 m a.s.l.). The monthly mean water balance shows a small deficit (7 mm) in summer and a substantial surplus (240 mm) between autumn and spring. The soil moisture regime is udic and the soil temperature regime is thermic. According to the classification of Thornthwaite (1948) the climate of the area is B1 B´2 r a´. Native vegetation is dominated by grasslands, largely modified by agriculture and grazing. The studied soils are polygenetic due to the geomorphologic evolution of the area. The sedimentary deposits include: a) transgressive deposits of the Querandinense ingression (humid climate) at the base; b) Postquerandinense eolian deposits (dry climate) and c) Postplatense deposits (dry climate) in the upper part. Pedons 2, 3, 4 and 5 have developed in loessial sediments. Unlike other carbonatic soils of the coastal plains, they are practically devoid of primary carbonate. On the other hand, Pedon 1 would have developed in a mixed deposit: an upper soil including shell fragments (Holocene), overlying a calcrete formed in a Pleistocene loessial deposit (Fig. 2, Table 1). The presence of pedogenic carbonate is revealed by macromorphological features such as pseudomycelia, soft powdery masses, some concretions and diffuse accumulations in root pores in the upper part of the solum, whereas the horizons overlying the rock contain lithogenic calcareous pebbles and shell fragments, as well as some pedogenic carbonates (soft powdery masses). Pedons 2, 3, 4 and 5 have a similar distribution of CaCO3 equivalent in depth. The carbonate is absent or has <1% in the upper horizons, it increases in the middle horizons and may reach 70% at the soil base or 80% in the coquina. The morphological and chemical characteristics of the calcareous accumulations allow the following horizons to be differentiated: a) calcium carbonate- enriched horizons (all pedons); b) calcic horizons (pedons 4 and 5) and c) petrocalcic horizons (pedons 1, 3 and 4). All of them exhibit calcareous reorganization. The former two are developed in the loessial deposits, whereas the latter are developed in the upper part of the coquina by epigenic alteration. Its contact with the overlying loessial sediments is sharp (<2 cm in thickness), with level or undulating shape, forming a compact, structureless (massive) or platy calcrete, less than 10 cm thick. The carbonate-enriched and calcic horizons have randomly distributed pedogenic acicular calcite (Fig. 3); the former with <15% and the latter with ?15% of CaCO3 equivalent. The petrocalcic horizons are massive or platy with ordered tabular calcite and rhombohedra and scalenohedra in rock holes, where CaCO3 equivalent can be as high as 60-70%. Grain-size distribution in pedons 2, 3 and 4 is similar and typical of the soils developed across the Undulating Pampa. The histograms show a well- defined mode in the coarse silt fraction (62-32 µm, 4-5 Ø) ranging from 24.01 to 25.34% in the eluvial horizons and from 14.17 to 22.42% in the illuvial horizons (Fig. 4). There is also a high amount of <1 µm clay (below 10 Ø), with 19.32-20.18% in the eluvial horizons and 22.90-52.17% in the illuvial horizons. The sand fraction is much lower, with fine and very fine sand as the dominant subfractions. The grain-size distribution of pedon 1 is almost uniform up to the loess deposit because illuvial horizons are absent. The mineralogy of the clay fraction in the loessial portion of Vertic Argiudolls (pedons 2 and 3) is mainly illitic, with well-defined reflections of this mineral and subordinate amounts of expandable minerals and kaolinite (Fig. 5). In addition to this general trend, a marked increase of expandable clays in B horizons was observed with respect to the A horizons. This would suggest, together with grain- size variations in the coarse fraction, a sedimentary discontinuity; thus, the soils of the area would have formed in two loess mantles with different grain-size composition and clay mineralogy. Micromorphological features revealed through optical microscopy include micritic and acicular calcite coatings and micritic nodular concentrations. SEM reveals recrystallization and dissolution morphologies in calcite crystals, which sometimes are found in the same horizon (Figs. 5, 6, 7). The pedons exhibit different crystallization morphologies; in the calcrete the cement has more or less equidimensional “rice grain”-shaped crystals and sparry and microsparitic calcite, whereas in the loessic horizons acicular calcite with variable morphology is mainly found. In the studied soils, acicular calcite presents different morphologies which may coexist in the same horizon: a) masses of disarranged crystals, 10- 50 µm long and 1 µm wide; b) needles with serrated irregular borders, c) complex morphologies of needles with serrated borders and irregular growths on the needles and, d) rhombohedric calcite en échelon. The calcrete in the petrocalcic horizons may present a laminar zone with tabular and rhombohedric calcite. The origin of pedogenic carbonate can be ascribed to various mechanisms, with different degree of influence: a) dissolution of carbonates in the upper part of the profile, downward translocation and precipitation; b) capillary rise and evaporation of carbonate water accumulated on the top of compact, almost impervious layers, c) in situ dissolution and reprecipitation of the coquina carbonates (petrocalcic horizons) and, d) biogenic precipitation due to the action of bacteria, fungi and plant roots, as a complementary process. The origin of the calcification process in the studied soils would be a mixed reorganization of the base rock and translocation under humid climate. In both cases the pedogenic carbonate would have had an abiotic origin with some biotic participation. Crystallization and recrystallization are dominant, either through dissolution of pre-existing deposits or through carbonate solutions moving vertically and laterally; biomineralization in organic structures has also an influence. In this way, the petrocalcic horizon is a pedogenic calcrete of humid climate.